Critical literacy in the Indonesian classroom: challenges and opportunities - RAMADHANI , Ahmad Arkam; JABU , Baso; Haryanto (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This research investigates the implementation of critical literacy strategies in an English as a Foreign Language (EFL) classroom by three English lecturers at the Universitas Muhammadiyah Bulukumba, Indonesia. The study aims to understand how these lecturers integrate critical literacy into their instruction and to identify the challenges encountered in this process. Data were collected through classroom observations and interviews involving three lecturers and 90 students, providing a comprehensive insight into their approaches and experiences. The findings reveal that the lecturers effectively employed the five-step instructional framework of critical literacy, which includes engaging students in questioning, facilitating group discussions, and encouraging them to read and think critically beyond the text. Despite relying on textbook materials, the lecturers successfully blended traditional teaching methods with critical literacy practices. By posing essential questions and fostering collaborative discussions, they created an environment that encouraged students to express their opinions freely. This approach not only enhanced students' critical thinking skills but also promoted social awareness, tolerance, and responsibility. However, the study also highlights several challenges in implementing critical literacy strategies. The primary challenge was the students' limited language proficiency, which hindered their ability to engage deeply with the texts and discussions. Additionally, transforming classroom practices to incorporate critical literacy proved difficult due to entrenched teaching methods and a lack of familiarity with critical literacy concepts. The lecturers also faced constraints related to inadequate teaching resources and facilities, which limited the effectiveness of their instruction.